Imports, exports, and jobs : what does trade mean for employment and job loss? - Kletzer, Lori G. (W.E. Upjohn Institute for Employment Research, 2002)
Annotation Kletzer attempts to heighten our understanding of the labor market costs of freer trade. While economy-wide net benefits may ensue from lossening trade policies, such policies do not proclude localized net losses. This book aims to measure some of these losses in the hope that future policy making will address them and the people who bear the burdon.